2018
DOI: 10.1016/j.jsv.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and experimental investigations of Modified Tuned Liquid Dampers (MTLDs)

Abstract: Tuned Liquid Dampers (TLDs), as passive control devices, have been used in high-rise buildings for vibration control. A TLD dissipates energy through the sloshing of the water inside the tank. Modified Tuned Liquid Damper (MTLD) utilizes the rotational spring system at the base, therefore the MTLD experiences both horizontal and rotational motions. In this study, MTLD-structure system subjected to sinusoidal excitation and seismic events has been investigated using Lu's analytical model. This analytical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Refs. [33,34] proposed a modified TLD design that incorporates an appropriate torsional spring connection to the floor instead of a rigid connection. They suggested that this modified TLD design is more effective than conventional designs.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [33,34] proposed a modified TLD design that incorporates an appropriate torsional spring connection to the floor instead of a rigid connection. They suggested that this modified TLD design is more effective than conventional designs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] A modified TLD connected by a rotational spring to the structure was proposed to enhance the liquid sloshing and wave breaking. [ 30,31 ] Tait and Deng [ 32 ] studied the performance of the TLDs with different tank geometry. Li et al [ 33 ] proposed a shallow cylindrical TLD to suppress the vibration of high rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [ 25 ] performed HIL simulation for tuned liquid column damper (TLCD) under seismic loads, and it was extended for multiple TLCDs. [ 26 ] Chang et al [ 27 ] also carried out an HIL simulation for demonstrating the effectiveness of a proposed modified TLD utilizing a rotational spring system at the base. Yet, application to an actual building considering wind loads and the similitude between the full‐scale and the model‐scale has not been introduced in such studies.…”
Section: Introductionmentioning
confidence: 99%